(untitled) (Al-Academy, 2020)
This study aimed at identifying how children express the emerging coronavirus in general and according to their age groups (4-13 years) by analyzing 91 of their drawings published online, using the descriptive content analytical approach. The results showed that children’s artistic expression of the virus came according to the concepts and ideas they carried about the virus for the age groups of (4-7 years) and (7-9 years), while it came according to visual perception for age groups (9-11 years), and from (11-13) years. Also, most children were aware about the presence of the virus and its widespread around the world, but (99%) of them do not realize the seriousness of the virus. It was confirmed that between (25-34%) of children were suffering from anxiety and fear from the virus, in addition to the lack of knowledge of children aged (4-7 years) of methods of prevention and safety from the virus, only (40%) of them valued the wearing of masks, followed by the importance of staying at home. The study also demonstrated the low percentages that were related to the extent of optimism of children to overcome the pandemic crisis.